2014
DOI: 10.1016/j.semcdb.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

MCM10: One tool for all—Integrity, maintenance and damage control

Abstract: Minichromsome maintenance protein 10 (Mcm10) is an essential replication factor that is required for the activation of the Cdc45:Mcm2-7:GINS helicase. Mcm10's ability to bind both ds and ssDNA appears vital for this function. In addition, Mcm10 interacts with multiple players at the replication fork, including DNA polymerase-α and proliferating cell nuclear antigen with which it cooperates during DNA elongation. Mcm10 lacks enzymatic function, but instead provides the replication apparatus with an oligomeric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 82 publications
(171 reference statements)
5
55
0
Order By: Relevance
“…In replication initiation, Mcm10 binds to single-stranded DNA (ssDNA) and promotes helicase activation, 49 and may recruit DNA polymerase-a primase to aid DNA elongation. 50 In view of its function in DNA replication, defects of Mcm10 may result in defective G1/S progression.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…In replication initiation, Mcm10 binds to single-stranded DNA (ssDNA) and promotes helicase activation, 49 and may recruit DNA polymerase-a primase to aid DNA elongation. 50 In view of its function in DNA replication, defects of Mcm10 may result in defective G1/S progression.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Heat-induced depletion of Mcm10 causes replication stress displaying the typical hallmarks of Rad53 phosphorylation and PCNA ubiquitination (Becker et al, 2014). SGA analysis identified SLX5 and SLX8 as top hits that exhibited synthetic sickness with the mcm10-1 allele at 30°C (Thu and Bielinsky, 2013, 2014). We validated the SGA results in a different genetic background and found that an approximately 100-fold growth defect in mcm10-1 slx5Δ mutants was apparent at 33°C compared to either single mutant (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…During the subsequent elongation step, Mcm10 is anchored to the Mcm2-7 complex, which comprises the core of the replicative Cdc45:Mcm2-7:GINS (CMG) helicase. It transiently interacts with DNA polymerase-α/primase and proliferating cell nuclear antigen (PCNA) both of which cycle on and off DNA during lagging strand synthesis (Thu and Bielinsky, 2014). Accordingly, depletion of Mcm10 compromises fork elongation, most notably at fragile sites of the human genome (Miotto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations